2001
DOI: 10.1679/aohc.64.281
|View full text |Cite
|
Sign up to set email alerts
|

Locations and Innervation of Cell Bodies of Sympathetic Neurons Projecting to the Gastrointestinal Tract in the Rat.

Abstract: The locations of cell bodies of sympathetic neurons projecting to the stomach, the duodenum, the ileum, the colon, the spleen and the pancreas have been studied using retrograde tracing. Projections arose from both pre- and paravertebral ganglia. In the rat, the prevertebral ganglia are the paired coeliac ganglia lying caudo-lateral to the root of the coeliac artery, paired splanchnic ganglia in the abdominal segments of the greater splanchnic nerves, unpaired superior mesenteric and inter-renal ganglia and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…Sympathetic axons extend along the lienal artery but fail to enter spleen parenchyma in the absence of NGF with concomitant elimination of Bax Another organ innervated by prevertebral ganglion sympathetic neurons is the spleen, which in rodents receives most of its sympathetic innervation from the celiac ganglion, with a minor contribution from the lower thoracic paravertebral sympathetic chain ganglia (Chevendra et al, 1991;Quinson et al, 2001). In contrast to other prevertebral ganglion targets described above, which showed a reduction in sympathetic innervation but not a complete elimination of sympathetic axons in the organs themselves, the spleen displayed a remarkable phenotype.…”
Section: Target Organs Of Prevertebral Sympathetic Ganglia Are Incompmentioning
confidence: 99%
“…Sympathetic axons extend along the lienal artery but fail to enter spleen parenchyma in the absence of NGF with concomitant elimination of Bax Another organ innervated by prevertebral ganglion sympathetic neurons is the spleen, which in rodents receives most of its sympathetic innervation from the celiac ganglion, with a minor contribution from the lower thoracic paravertebral sympathetic chain ganglia (Chevendra et al, 1991;Quinson et al, 2001). In contrast to other prevertebral ganglion targets described above, which showed a reduction in sympathetic innervation but not a complete elimination of sympathetic axons in the organs themselves, the spleen displayed a remarkable phenotype.…”
Section: Target Organs Of Prevertebral Sympathetic Ganglia Are Incompmentioning
confidence: 99%
“…Approximately 95% of sympathetic postganglionic neurons innervating this vascular bed in the rat have their cell bodies in the celiac and superior mesenteric ganglia. [12][13][14] …”
mentioning
confidence: 99%
“…Approximately 95% of sympathetic postganglionic neurons innervating this vascular bed in the rat have their cell bodies in the celiac and superior mesenteric ganglia. [12][13][14] These 2 ganglia are fused in the rat and are commonly referred to as the celiac or solar plexus. 15 We used surgical ablation of this plexus (celiac ganglionectomy [CGx]) to investigate our hypothesis.…”
mentioning
confidence: 99%
“…Viscerotopic organization of the spinal sensory innervation of the duodenum is slightly different in various animal species, but in general the innervation extends from segments T2-L3, with the peak innervation occurring between segments T9 and L1 (Khurana and Petras, 1991;El Ouazzani and Mei, 1978;Hazarika et al 1964;Cottrell and Greenhorn, 1987;DeLeo et al, 1991;Quinson et al 2001). Furthermore, anatomical studies indicate variable degrees of overlap in sensory projections from both the stomach and duodenum to spinal ganglia and segments.…”
Section: Locations Of Neuronsmentioning
confidence: 99%
“…In general, it is believed that vagal afferents from the duodenum may play a role in conveying digestive information, such as absorption, secretion, and storage; whereas, nociceptive information mainly travels via the splanchnic sympathetic afferent nerves to the spinal cord. Anatomic studies have shown that splanchnic afferent fibers from the duodenum mainly project to the caudal thoracic and upper lumbar spinal cord in various species (Cottrell and Greenhorn 1987;DeLeo et al 1991;El Ouazzani and Mei, 1978;Hazarika et al 1964;Khurana and Petras 1991;Quinson et al 2001). However, to the best of our knowledge, no electrophysiological study has been done to examine the activity of spinal neurons receiving duodenal afferent input.…”
Section: Introductionmentioning
confidence: 99%